Political public relations in digital health communication: Engagement and trust building - Amir, Andi Subhan; Pangkam, Moti (PRofesi Humas, 2025)
Background: The increasing complexity of health crises in the digital era has heightened the need for effective communication strategies that not only inform but also build trust. Political Public Relations (Political PR) has emerged as a central actor in framing public understanding and shaping behavior in response to government-led health campaigns. Purpose: This study explores how Political PR strategies are utilized in digital health communication to influence public trust and engagement. Methods: Employing a qualitative-comparative method, this research analyzes two case studies—Indonesia and Country X—focusing on the effectiveness, framing, and ethical dimensions of Political PR campaigns. Results: The findings reveal that Political PR strategies that emphasize credibility, transparency, and interactive communication, especially those involving health experts, tend to foster stronger public engagement. Platforms like Instagram and YouTube are more effective than text-heavy media such as Twitter, particularly when messages are framed empathetically and supported by trusted sources. However, ethical challenges such as misinformation, political bias, and the use of non-expert influencers pose risks to public trust. Conclusion: The study highlights the critical need for campaigns to integrate evidence-based messaging, collaborative communication, and ethical standards. Implications: This research contributes to both theoretical and practical understandings of Political PR in health communication by offering insights on strategy development, public trust dynamics, and platform effectiveness. The findings are expected to guide future political communication efforts during public health emergencies in digital contexts.